FAKTOR-FAKTOR YANG MEMPENGARUHI PENDIDIKAN KARAKTER HOLISTIK SISWA SMKN DI KOTA MALANG - Dianna Ratnawati (Universitas Sarjanawiyata Tamansiswa, 2015)
Facing the challenge of MEA, we require to filter for protecting the foreign cultures that are not the same with the culture of our nation, one of the solutions is a holistic character education. This study is for determining the effect of: (1) the family environment and the industrial work practice towards holistic character education, (2) the family environment and the industrial work practice towards the soft skills, and (3) the family environment and the industrial work practice indirectly through soft skills towards the holistic character education. This type of research is the ex-postfaco to with quantitative approach. The technique of collecting data using questionnaires. While the analysis technique using path analysis. The research population numbered 555 students of vocational hight school in Malang, and 126 students for sample. Sampling uses a random probability sampling group. The results showed: (1) there is a direct effect and significant correlation between family environment and industrial work practice towards holistic character education, (2) there is a direct influence of the family environment and the industrial work practice against soft skill, and (3) there is the indirect effect between family environment and industrial work practice through the soft skills of the holistic character education.